Development of rotavirus A VP6-based fusion protein (RVP6) and VP6-specific IgY (RVP6-IgY) safety, immunogenicity and efficacy in animal models - Balolong, Marilen P. 1974- (2014)
Because of the widespread nature of diarrheal diseases caused by rotavirus and the similarity of morbidity rates among developed and developing countries, effective vaccines are considered key to their control. Intrinsic limitations and emerging potential deficiencies of live rotavirus vaccines have prompted the tapping of non-living rotavirus vaccine candidates including rotavirus viral proteins. One promising candidate, VP6, is highly immunogenic and majority of antibody generated in an infected individual is directed against this protein. Serum IgY of laying hens, under natural conditions is deposited in large quantities in the egg yolk in order to protect the developing embryo from potential pathogens. Thus, it is possible to immunize the hen with purified VP6 to produce IgY with activity against these specific disease conditions. This study developed vaccine molecules based on rotavirus VP6 gene to test its utility as an alternative molecule (to whole live attenuated forms available) for active immunization, and to generate RVP6-specific-IgY for passive immunization. Safety was determined by noting significant changes in body weight and other physical manifestations among immunized mice relative t the non-immunized control. Immunogenicity was verified by monitoring rise in serum and fecal antibody titers among immunized mice relative to the non-immunized control. Efficacy was evaluated by reduction in fecal shedding of which greater than 50% reduction was considered efficacious. RVP6 was used to immunize laying hens, to generate RVP6-IgY. Immunogenicity was measured by monitoring rise in serum and yolk IgY antibody titers relative to the non-immunized hens. RVP6-specific IgY recovered in the yolk was purified and was used for passive immunization. Efficacy of RVP6-IgY was likewise evaluated by reduction in fecal shedding. Overall, oral delivery of RVP6 vaccine molecule was shown to be well tolerated, immunogenic and efficacious against rotavirus challenge. Since no physical changes and decrease in respective body weights of mice were noted, this suggested the safety of RVP6 as a vaccine molecule. RVP6 immunization elicited strong immune responses relative to the non-immunized group in terms of serum IgG and fecal IgA that correlated with the resulting 86.5% reduction in virus shedding. Previous similar studies have supported the ability of VP6 to protect mice following challenge due to its capacity to inhibit viral replication intracellularly as correlated with the production of antibodies both in serum and in feces. The amount of RVP6-IgY recovered from yolk following hyperimmunization with RVP6 was generally proportional to the serum IgY produced per time period. A concentration of 200mcg RVP6 antigen introduced intramuscularly was found to be optimal in producing significant titers of IgY that were subsequently recovered from yolk by 6 weeks post immunization. RVP6-IgY as a passive immunization molecule effectively reduced viral shedding in feces up to 70.5% at 24 hours post-virus inoculation and post-immunization relative to the non-immunized control. Findings suggest protection by RVP6-IgY as a passive immunization molecule as supported by the absence of histopathologic lesions as well as tumor-associated growth from the respective tissues studied. Previous studies have also supported our findings owing to the ability of RVP6-specific antibodies/ RVP6-IgY to effectively inhibit viral replication and cease fecal shedding to stop the spread of infection. Overall, VP6-based vaccine molecules can serve as alternative to the whole live attenuated vaccines available as it was found to be safe, immunogenic and efficacious.